Israeli Demonstration Posters: Spatial Semiotics of Silence - Ornan-Ephratt, Michal (Semiotika, 2024)
Israel’s coalition effort (2023) to introduce a “(judicial) reform” was perceived by many Israelis as endangering Israel’s standing as a democratic state. The salience of silence as a theme and a form in the posters exhibited in the demonstrations supporting and opposing the coalition’s move triggered the examination of the semiotic roles played by silence in those posters and whether this use of silence differed by reform support/opposition. Two-hundred and twenty posters partaking in the demonstrations’ linguistic landscape were examined. Implementing an algorithm based on Ephratt’s (2022) model for identifying different types of silences revealed that fifty six of the posters alluded to one of the six categories of silence (stillness, symptomatic silences, silencing, pauses, the unsaid or verbal silence). These posters served as the data for a qualitative-thematic methodology, iteratively abstracting semiotic roles. Silences and silencing reoccurred as a theme concerning political discourse, particularly the matter of voice. The need for parsimonious use of crucial signantia on posters transformed into a semiotic strategy in which leaving out expected signantia served iconically to communicate absence, conatively activate the observers or express consent, metalinguistically convey the shortage of words, legally circumvent possible charges and create a hiatus that provides soothing qualities, enhancing in-group and out-group tolerance. The differing use of silence in the posters, depending on reform support/opposition, is explained in terms of horror vacui and motivation. Finally, the individual posters, as material texts, did not appear nor function in isolation: they took an active part in producing the demonstrations’ spatial semiotics.